Literasi Digital dan Pemahaman Konsep Himpunan Siswa SMP Menggunakan Media Pembelajaran GUI Matlab - Ayu Raihanah; Octavina Rizky Utami Putri; Moh. Mahfud Effendi (Jurnal Elemen, 2020)
The purposes of this research are to analyze the digital literacy of students in using the GUI Matlab learning media and understanding the concept of set in junior high school students through digital literacy using the GUI Matlab. To answer these problems using a qualitative approach. The subjects of this study were five students of class VII tutoring. The research instruments used in this study were a test, an interview, and a questionnaire. Data are analyzed by reducing data, presenting narrative data, and concluding results. The results of this study show that the digital literacy of students in using GUI Matlab learning media is excellent. Besides, 80% of students can determine the members of the set correctly, 80% of students can determine the empty set correctly, 100% students can draw Venn diagrams correctly, determine the set of complements correctly, and determine the subset.